mmWave zero order resonant antenna with patch-like radiation fed by a Butler matrix for passive beamforming - Mohan, Manoj Prabhakar (2024)
A small zero-order resonant antenna based on the composite right-left-handed (CRLH) principle is designed and fabricated without metallic vias at 30 GHz to have patch-like radiation. The mirror images of two CRLH structures are connected to design the antenna without via holes. The equivalent circuit, parameter extraction, and dispersion diagram are studied to analyze the characteristics of the CRLH antenna. The antenna was fabricated and experimentally verified. The measured realized gain of the antenna is 5.35 dBi at 30 GHz. The designed antenna is free of spurious resonance over a band width of 10 GHz. A passive beamforming array is designed using the proposed CRLH antenna and the Butler matrix. A substrate integrated waveguide is used to implement the Butler matrix. The CRLH antennas are connected to four outputs of a 4×4 Butler matrix. The scanning angles are 12∘, -68∘, 64∘, and -11∘ for excitations from port 1 to port 4 of the 4×4 Butler matrix feeding the CRLH antenna.